The effect of giving the five-finger hypnosis technique on reducing pain intensity in Gastroesophageal Reflux Disease (GERD) patients at the health center Adi Luhur Mesuji - Ardinata Ardinata; Feri Agustriani; Nirwana Nirwana; Rice Hernanda; Andi Susanto (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Pain problems that are often experienced by patients when visiting health facilities are gastroesophageal reflux disease (GERD). The impact of untreated GERD causes sleep quality, stress, anxiety, and the emergence of feelings of fear, and will have an impact on prolonged pain. Non-pharmacological management of GERD can be done with 5 finger hypnosis. The purpose of this study was to determine the effect of giving the five-finger hypnosis technique on reducing pain intensity in gastroesophageal reflux disease (GERD) patients at health center Adi Luhur Mesuji year 2022. This type of research is quantitative using a pre-experimental research design with a one grup pretest and posttest design. This research was conducted at the Adiluhur Health Center on 8 December 2021 to 10 January 2022. The sample in this study was 30 GERD patients. The sampling technique used in this study was accidental sampling. Analysis of the data used using the mann whitney test. The results of the analysis showed that there was an effect of giving the five finger hypnosis technique on reducing pain intensity in gastroesophageal reflux disease (GERD) patients, with a p-value of 0.042 (less than 0.05). It is hoped that the results of this study will increase knowledge about the effect of giving five-finger hypnosis techniques on reducing the intensity of GERD pain and then increasing non-pharmacological treatment while pain can be overcome.Abstrak: Masalah nyeri yang banyak dialami oleh pasien ketika berkunjung ke fasilitas Kesehatan adalah gastroesophageal refluks disease (GERD). Dampak dari GERD yang tidak ditangani menyebabkan kualitas tidur, stres, ansietas, dan timbulnya perasaan takut, dan nyeri yang berkepanjangan. Penanganan GERD secara non-farmkologis dapat dilakukan dengan hypnosis 5 jari. Tujuan dari penelitian untuk mengetahui pengaruh pemberian tekhnik hipnosis lima jari pada penurunan intensitas nyeri pada pasien gastroesophageal refluks disease (GERD) Puskesmas Adi Luhur Kabupaten Mesuji tahun 2022. Jenis penelitian ini adalah kuantitatif dengan menggunakan design penelitian pre eksperimantal design pendekatan penelitian one grup pretest and posttest design. Penelitian ini telah dilakukan di Puskesmas Adiluhur pada tanggal 8 Desember 2021 sampai dengan 10 Januari 2022. Sampel dalam penelitian ini sebanyak 30 pasien GERD. Pengambilan sampel menggunakan acidental sampling. Analisa data menggunakan uji mann whitney. Hasil analisis menunjukan terdapat pengaruh pemberian tekhnik hipnosis lima jari pada penurunan intensitas nyeri pada pasien gastroesophageal refluks disease (GERD) didapat p-value 0,042 (kurang dari 0,05). Diharapkan hasil penelitian ini menambah pengetahuan tentang pengaruh pemberian tekhnik hipnosis lima jari pada penurunan intensitas nyeri GERD kemudian meningkatkan pengobatan non farmakologi selagi nyeri dapat diatasi.